1999
DOI: 10.1046/j.1365-2362.1999.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurone‐specific enolase and N‐acetyl‐aspartate as potential peripheral markers of ischaemic stroke

Abstract: Serum N-acetyl-aspartate appears to be an early peripheral marker of ischaemically affected brain neurones, and the ratio of N-acetyl-aspartate to a protein marker, such as NSE, may serve as an index of irreversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
2
31
0
2
Order By: Relevance
“…Previous studies have reported increased plasma or serum neurobiochemical markers, e.g., S-100 protein, neuron-specific enolase, and N-acetylaspartate, in the peripheral circulation of patients after stroke but failed to demonstrate that these markers offered any additional advantage over current clinical assessment scales, risk factors, or neuroradiologic techniques (5)(6)(7)(8). Correlations have been observed between marker values, infarct size, and NIHSS scores, and increased concentrations predict disability and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported increased plasma or serum neurobiochemical markers, e.g., S-100 protein, neuron-specific enolase, and N-acetylaspartate, in the peripheral circulation of patients after stroke but failed to demonstrate that these markers offered any additional advantage over current clinical assessment scales, risk factors, or neuroradiologic techniques (5)(6)(7)(8). Correlations have been observed between marker values, infarct size, and NIHSS scores, and increased concentrations predict disability and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The blood-brain barrier is compromised in many patients with stroke, and the liberation of neurobiochemical protein markers into the circulation may allow the pathophysiology, progress, and prognosis of patients with cerebrovascular disease to be further evaluated (5)(6)(7)(8). Although increased concentrations of several neurobiochemical protein markers have been detected in the peripheral blood of patients with stroke, to date none has found a place in clinical practice.…”
mentioning
confidence: 99%
“…Animal experiments have verified that plasma NSE begins rising within 2 hr of ischemia, and continues for 2.5 days (Barone et al., 1993). Stevens, Jakobs, de Jager, Cunningham, and Korf (1999) observed that in 19 patients with acute cerebral embolism, serum NSE levels increased within 4 hr of the attack. Gruener, Gross, Gozlan, and Barak (1994) found that NSE levels in blood and CSF of patients with acute stroke reached peak values after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens et al [12], Hill et al [13], Schaarschmidt et al [14] have demonstrated an increase in serum NSE level after acute focal ischemia in humans.…”
Section: Discussionmentioning
confidence: 99%